2004
DOI: 10.1074/jbc.m401413200
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3β Regulates Growth, Calcium Homeostasis, and Diastolic Function in the Heart

Abstract: Glycogen synthase kinase (GSK) 3␤ is a negative regulator of stress-induced cardiomyocyte hypertrophy. It is not clear, however, if GSK-3␤ plays any role in regulating normal cardiac growth and cardiac function. Herein we report that a transgenic mouse expressing wild type GSK-3␤ in the heart has a dramatic impairment of normal post-natal cardiomyocyte growth as well as markedly abnormal cardiac contractile function. The most striking phenotype, however, is grossly impaired diastolic relaxation, which leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
106
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 57 publications
11
106
2
1
Order By: Relevance
“…ANT, VDAC, CypD). Moreover, we cannot fully exclude a contribution of SERCA2 since Michael et al 12 previously demonstrated that overexpression of GSK3β could significantly reduce the expression of SERCA2 in the heart. 12 We noticed in the present work that SERCA2 expression seems to be increased when GSK3β was inhibited at the onset of reperfusion (data not shown).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…ANT, VDAC, CypD). Moreover, we cannot fully exclude a contribution of SERCA2 since Michael et al 12 previously demonstrated that overexpression of GSK3β could significantly reduce the expression of SERCA2 in the heart. 12 We noticed in the present work that SERCA2 expression seems to be increased when GSK3β was inhibited at the onset of reperfusion (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, we cannot fully exclude a contribution of SERCA2 since Michael et al 12 previously demonstrated that overexpression of GSK3β could significantly reduce the expression of SERCA2 in the heart. 12 We noticed in the present work that SERCA2 expression seems to be increased when GSK3β was inhibited at the onset of reperfusion (data not shown). Such mechanism remains to be investigated in-depth in future studies, especially since a problem of timing has to be considered between the speed of Ca 2+ response and the time needed for SERCA2 protein transcription at the onset of reperfusion.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…GSK-3β is a well-characterized regulator of cytoplasmic β-catenin level. Recent study has shown that cardiac overexpression of wild type GSK-3β inhibits postnatal physiological growth [6]. The deficiency in cardiac growth lies in the defect of cardiac myocytes to growth in cell diameter, while myocyte growth in length is maintained or even enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutively active GSK-3β attenuates cardiac hypertrophy by phosphorylating the nuclear factor of activated T cells (NFAT) and inhibiting its nuclear translocation. Similarly, the overexpression of wild-type GSK-3β in the heart also inhibits cardiac hypertrophy [5], most likely through the reduction of cytoplasmic β-catenin levels in cardiac myocyte [6]. Interestingly, wild-type GSK-3β also inhibits postnatal physiological growth in addition to pathological hypertrophy.…”
Section: Introductionmentioning
confidence: 99%